Pemetaan Peran Pemerintah Dalam Mengakselerasi Pengembangan Perbankan Syariah di Indonesia: Studi Kasus Otoritas Jasa Keuangan dan Bank Indonesia - Isfandayani . (MASLAHAH (Jurnal Hukum Islam dan Perbankan Syariah), 2013)
The bank regulation and controlling will shift from Bank of Indonesia (Bl) and the Financial Services Authority (Otoritas Jasa Keuangan/OJK) commencing on 31 December 2013. It will be very interesting to be analyzed In the form of mapping of the government role to accelerate the Islamic Banking in Indonesia by using the Bl and OJK case study. The research explains the BI-OJK authority, the Bi-OJK coordination, the Islamic Banking development, the difference of BI-OJK from the Islamic banking view, from the analysis of 81 transfer to OJK needs proper preparation mainly the competent human resource in Islamic Banking